Site investigation, sampling and slope stability analysis at kilometer 141 KL-Kuantan highway - Audi Munir, Mahmud (2011)
Recently, the public become more concern about slope failure and landslide. Beside that, the governments try to limit any construction at high risk slope area and enforce the construction at high risk slope to provide ground improvement and slope reinforcement. This response is due to the landslide problem that happened frequently in year 2008. In response to the rising problems, this study has been proposed for the Final Year Project. The objective of this Final Year Project is to determine the basic properties, shear strength and unit weight of slope which is located at kilometer 141 from KL-Kuantan Highway. The analysis then will determine the better option between soil nail and anchor reinforcement since these two methods are commonly used. Based on particle size distribution, the soil at three part of slope are dominant by sandy soil type. The moisture content result for the slope is range 22% to 26%. For plastic limit result, the range is 21% to 25% and for liquid limits results, the range is 43% to 50%. The range of dry unit weight is 11kN/m 3 3 to 12kN/m with optimum moisture content is 13% to 18%. Based on this result, toe the slope is the most dense part since the dry unit weight is the highest and lowest optimum moisture content. The average shear strength for lower layer is higher than upper layer which is 93.49kPa for lower layer and 71.76kPa for the upper layer. By using slope/W software, the factor of safety (FOS) of existing slope is determined, which is 2.044. Beside that, analysis shows that soil nail reinforcement will give the higher FOS rather than using anchor reinforcement which is 2.940 for soil nail reinforcement and 2.847 for anchor reinforcement. This probably because the soil nails have a lower load requirement than tieback anchors, and are placed closer together.